Growing Markets through Business Training for Female Entrepreneurs: A Market-Level Randomized Experiment in Kenya - David McKenzie; Olga Susana Puerto (Institute of Labor Economics (IZA), 2017)
A common concern with efforts to directly help some small businesses to grow is that their growth comes at the expense of their unassisted competitors. We test this possibility using a two-stage randomized experiment in Kenya which randomizes business training at the market level, and then within markets to selected businesses. Three years after training, the treated businesses are selling more, earn higher profits, and their owners have higher well-being. There is no evidence of negative spillovers on the competing businesses, and the markets as a whole appear to have grown in terms of number of customers and sales volumes. This market growth appears to come from enhanced customer service and new product introduction, generating more customers and more sales from existing customers. As a result, business growth in underdeveloped markets is possible without taking sales away from non-treated businesses.
Keywords: O12; O17; J16; L26; 330; business training; spillovers; microenterprise; market development